2016
DOI: 10.4067/s0718-58392016000400006
|View full text |Cite
|
Sign up to set email alerts
|

Control of weeds in glasshouse and rice field conditions by phytotoxic effects of Tinospora crispa (L.) Hook.f. & Thomson leaves

Abstract: Phytotoxic potential of powder and methanol extract of Tinospora crispa (L.) Hook. f. & Thomson leaves as pre-and post-emergence applications on the growth of transplanted rice (Oryza sativa L.) and associated weeds were evaluated under glasshouse and field conditions to determine its herbicidal activity as soil additive material in rice fields. In glasshouse study, utilization of leaf powder and leaf extract of T. crispa as pre-emergence application provided a satisfactory weed control, inhibiting seed germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Our study confirms previous results with regards to the herbicidal effect of EOs, which would recommend them as natural herbicides in organic farming. Regarding the allelopathic effect of EOs in connection with wheat germination, previous studies have shown that wheat cultivars were less affected compared to weed species, suggesting the possibility to use these natural compounds—in proper doses—as bioherbicides for weed control [40,41]. However, the germination inhibition rate of rosemary EO for wheat cultivars ranged between 10.3% and 78.5%, when the concentration dose was in the range of 2 to 16 μL.…”
Section: Resultsmentioning
confidence: 99%
“…Our study confirms previous results with regards to the herbicidal effect of EOs, which would recommend them as natural herbicides in organic farming. Regarding the allelopathic effect of EOs in connection with wheat germination, previous studies have shown that wheat cultivars were less affected compared to weed species, suggesting the possibility to use these natural compounds—in proper doses—as bioherbicides for weed control [40,41]. However, the germination inhibition rate of rosemary EO for wheat cultivars ranged between 10.3% and 78.5%, when the concentration dose was in the range of 2 to 16 μL.…”
Section: Resultsmentioning
confidence: 99%